Nigerian Youths: The Endangered Specie - Ejogba, Orhero Abraham; Chuks, Okolie Ugo (Master Program of Sociology, Universitas Malikussaleh,, 2023)
The youth of Nigeria, who were previously vital to the nation's potential, are now facing a crucial turning point. They encounter numerous obstacles that classify them as an endangered species. This research aims to investigate the factors endangering the future of our nation's youth, who are its hope and lifeblood, as well as how youth endangerment can be mitigated. A qualitative research design was used in this study to understand better the nature and character of youth endangerment in Nigeria. This theoretical study relied on secondary data from books, journal articles, and other publications to back up its claims. Multiple secondary sources were used to reduce the possibility of error and improve the study's reliability and validity. The study concludes that the most frustrating situation for Nigerian youth has been a lack of employment, which has pushed many youths to seek alternatives to salvage their economic situation, and concrete recommendations to reduce youth endangerment in Nigeria were made.